2019
DOI: 10.1016/j.pmedr.2019.100957
|View full text |Cite
|
Sign up to set email alerts
|

US oral health students' willingness to train and administer the HPV vaccine in dental practices

Abstract: HPV oropharyngeal cancers have now surpassed cervical cancer rates in the US. Dental providers' engagement in HPV education and vaccination efforts may help reduce the burden of HPV oropharyngeal cancers. We examined factors associated with oral health students' willingness to train and administer the human papillomavirus (HPV) vaccine in dental settings. US students in 15 oral health programs participated in an online survey in 2016. Unadjusted and adjusted multivariable logistic regression were conducted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
(38 reference statements)
1
23
1
Order By: Relevance
“…Nearly 88% of the students correctly identified HPV as a risk factor for oropharyngeal cancer development, compared to only 9.39% in the present study [14]. Another study by Kepka et al revealed that up to 83.7% of oral health students believed that administering HPV knowledge and vaccination fell within the scope of practice of dental professionals, encouraging their participation in eradicating this virus [15].…”
Section: Discussioncontrasting
confidence: 57%
“…Nearly 88% of the students correctly identified HPV as a risk factor for oropharyngeal cancer development, compared to only 9.39% in the present study [14]. Another study by Kepka et al revealed that up to 83.7% of oral health students believed that administering HPV knowledge and vaccination fell within the scope of practice of dental professionals, encouraging their participation in eradicating this virus [15].…”
Section: Discussioncontrasting
confidence: 57%
“…Percentage of response agreed vaccines were effective (~97%), significantly fewer dental students agreed they were safe [13]. Although one recent study found that further education and training would improve willingness of dental providers to discuss and recommend HPV vaccination, previous work from the same group found dental knowledge, awareness and willingness may be more malleable than established dental providers [14][15][16]. It was also found that the awareness among dental students was comparatively lesser than postgraduate students which may be due to the increased experience according to Mann et al ' [13].…”
Section: Resultsmentioning
confidence: 99%
“…The few previous studies that evaluated the awareness, knowledge and acceptance of HPV vaccination among dental students and post-graduate residents found deficiencies in both knowledge and awareness [15][16][17][18]. This study evaluated both dental student and post-graduate resident awareness, knowledge and acceptance of HPV vaccination during a curricular module devoted to immunization practices and HPV-specific vaccination and found noteworthy similarities and differences.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the finding that nearly twice the percentage of dental students (approximately 20%) compared with dental residents (approximately 10%) agreed that some vaccines were dangerous may suggest that these concerns about vaccine safety, in general, may be more widespread and must be addressed within the dental school curriculum [23,24]. Although one recent study found that further education and training would improve willingness of dental providers to discuss and recommend HPV vaccination, previous work from the same group found dental student knowledge, awareness and willingness may be more malleable than established dental providers [17,18,25]. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation